Copper only SOD repeat proteins likely act as an extracellular superoxide dismutase in oyster antioxidant defense - Li Tan; Youli Liu; Yueyang Sun; Sheng Liu; Zhihua Lin; Qinggang Xue (Scientific Reports)
Abstract Superoxide dismutases (SODs) are key enzymes involved in oxidative stress regulation. In most eukaryotes, they typically require both copper and zinc for catalysis and structural stability. However, copper-only SODs, previously identified in bacteria and fungi, represent a novel enzyme class with unique catalytic mechanisms. This study investigates copper-only SOD-repeat proteins (CSRPs) in two oyster species, Crassostrea gigas and Crassostrea sikamea, marking the first functional evidence of these proteins as extracellular SODs. Three CSRP genes were identified in each species, with expression localized primarily to the mantle. Structural modeling of a representative protein, Cs-CSRP1, revealed conserved copper-binding sites essential for SOD activity. Functional assays using recombinant Cs-CSRP1 confirmed its SOD activity, supporting its role as a novel extracellular antioxidant enzyme. These findings offer new insights into oyster antioxidant defense mechanisms and the evolution of SOD family proteins.